Studies in classical linguistics in honor of Philip Baldi - Page, B. Richard.; Rubin, Aaron D., 1976-; Baldi, Philip. (Amsterdam Studies in Classical Philology, 2010)
This volume includes fourteen original articles, written by a diverse group of distinguished scholars in honor of Philip Baldi (Penn State University). The contributions all focus on some aspect of classical linguistics, by which is meant Latin, Greek, Etruscan, and Indo-European. Some focus more on historical linguistic issues, while others deal with synchronic grammatical or semantic problems. The volume also offers a complete bibliography of the works of Philip Baldi, as well as a personal sketch.